Popov Mikhail Andreyevich (1903—1986). To the 100th birthday - O. A. Ivchenko; S. F. Fominykh; G. I. Mendrina; M. V. Gribovsky (Бюллетень сибирской медицины, 2003)
The biography of an honored doctor of RF, a head surgeon of Tomsk region (1953—1967) and a reader of Tomsk Medical Institute (today SibSMU) M.A. Popov has been presented.